World Bank East Asia and Pacific Economic Update 2011, volume 2 navigating turbulence, sustaining growth. - World Bank (Washington, D.C. The World Bank, 2011)
The World Bank East Asia and Pacific Economic Update is a comprehensive, twice-yearly review of the region's economies prepared by the East Asia and Pacific region of the World Bank. In this edition, the report notes that real GDP growth in East Asia has been moderating after a sharp rebound from the global crisis. Inflation has become the key short-run challenge for the authorities in the region, complicated by a surge in portfolio capital inflows and rapidly increasing food and commodity prices that hit low-income households disproportionately. Over the medium-term, East Asia has the potential to sustain rapid increases in living standards even as the global economy enters a more challenging phase.
Keywords: Economic indicators -- East Asia; Economic indicators -- Pacific Area; aEconomic indicators -- Southeast Asia